KLASIFIKASI ARTIKEL-ARTIKEL JURNAL PUSTAKALOKA BERDASARKAN SKEMA JITA - Faisal Syarifudin (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
This research aims to determine the classification of articles in journal of Pustakaloka, and specifically to identify the largest and smallest subject groups based on JITA Classification System of Library and Information Science. Data for this research consist of 174 articles from 2009-2021 publication. To assign the subject of an article, its title and keywords were analyzed. Abstract and article content were also analyzed if the title and keywords were not able to reflect the subject. The data were coded according to the JITA scheme, sorted and counted to build up subject groups. The three largest subject groups are Users, literacy and reading, followed by Information sources, supports, channels, then by Management and Information technology and library technology. Meanwhile, the three smallest subject groups are Information use and sociology of information, followed by Theoretical and general aspects of libraries and information, Housing technologies, and the last is Publishing and legal issues. This research identified that in general, the articles in Pustakaloka are concentrated on some of intermediate and specific level that cover the aspect of users, directional and management functions, pragmatic and technical issues.